2017
DOI: 10.1177/2041386617705434
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation in entrepreneurs

Abstract: Psychological processes (e.g., cognition, motivation, emotions) have emerged as key to understanding entrepreneurial actions and success. Currently, we do not know enough about specific entrepreneurial psychological processes and particularly lack knowledge about their cumulative or interactive effects. Self-regulation offers some promise in understanding these issues. However, self-regulation in entrepreneurship has not been fully explored, which limits our understanding. We address this by introducing an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 146 publications
(310 reference statements)
2
22
0
Order By: Relevance
“…These findings are in accordance with past research, which suggested that entrepreneurial traits have an important impact on entrepreneurial intention (Shu et al, 2016). This study introduces entrepreneurial emotion into the framework of the relationship between cognition and behavioral intention and expands the research on emotion in the field of entrepreneurship (O'Shea et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in accordance with past research, which suggested that entrepreneurial traits have an important impact on entrepreneurial intention (Shu et al, 2016). This study introduces entrepreneurial emotion into the framework of the relationship between cognition and behavioral intention and expands the research on emotion in the field of entrepreneurship (O'Shea et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Past studies have demonstrated that positive emotions can be used as additional information to help individuals understand the difficulties optimistically (Huxtable- Thomas et al, 2016;O'Shea et al, 2017). This greatly reduces the risk that enterprise founders perceive in the entrepreneurial process, allowing them to assume that they can control the uncertainties and outcomes of internal and external environments, so that they can make the appropriate entrepreneurial decisions quickly.…”
Section: The Mediating Role Of Emotional Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, in the context of a country with a large environmental differentiation, such differences will be more obvious. The entrepreneurial traits possessed by individuals are closely related to their psychological behaviors (O'Shea et al, 2017). To analyze entrepreneurship education from a psychological perspective, the element of entrepreneurial self-efficacy is an important embodiment of personality psychological traits, both in terms of tasks and fields (Cho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that for the most part sleep occurs in the home domain, our research introduces a spillover lens (i.e., experiences being transferred intact between domains; Edwards & Rothbard, 2000) to examine the home-to-work spillover of sleep to employee effectiveness. To fully explain this spillover we draw on the distinction between cognitive-, affective-and motivational processes (Inzlicht & Schmeichel, 2012;Lazarus, 1991;O'Shea et al, 2017) and hence test the mediating role of regulatory resource availability, positive affect, and subjective vitality in the relation between sleep and employee effectiveness.…”
mentioning
confidence: 99%